E-Learning as a Learning Media in Primary Schools during Pandemic - Amanah Dwi Wahyuni (Community Medicine and Education Journal, 2021)
Currently, the world is faced with an outbreak of a disease caused by a virus known as covid 19. Along with the high number of positive cases of covid 19 in Indonesia, the government is urging to deal with this covid 19 pandemic immediately. Various policies have been carried out, such as implementing physical distancing, lockdown, and the 5M movement. The existence of these policies certainly impacts most aspects of life, especially in the education aspect. Learning that is usually done face-to-face becomes impossible. So that the government issues a policy so that the learning process can be implemented. One of the solutions offered by the government is to change face-to-face learning into online learning (in the network) using e-learning sites. E-Learning media is supported by various learning features that are made like face-to-face learning.